2013
DOI: 10.1063/1.4773011
|View full text |Cite
|
Sign up to set email alerts
|

Linear scaling explicitly correlated MP2-F12 and ONIOM methods for the long-range interactions of the nanoscale clusters in methanol aqueous solutions

Abstract: A linear scaling quantum chemistry method, generalized energy-based fragmentation (GEBF) approach has been extended to the explicitly correlated second-order Møller-Plesset perturbation theory F12 (MP2-F12) method and own N-layer integrated molecular orbital molecular mechanics (ONIOM) method, in which GEBF-MP2-F12, GEBF-MP2, and conventional density functional tight-binding methods could be used for different layers. Then the long-range interactions in dilute methanol aqueous solutions are studied by computin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…[135][136][137][138][139] The combination of explicitly correlated approaches with local methods has been particularly successful. 49,50,53,76,135,[140][141][142][143][144][145][146][147] It has been found that the F12 terms not only reduce the basis set incompleteness errors, but also implicitly account for excitations to the orbitals outside the domains, 140,141 and therefore reduce the domain errors significantly. This strongly improves the accuracy and robustness of the local methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[135][136][137][138][139] The combination of explicitly correlated approaches with local methods has been particularly successful. 49,50,53,76,135,[140][141][142][143][144][145][146][147] It has been found that the F12 terms not only reduce the basis set incompleteness errors, but also implicitly account for excitations to the orbitals outside the domains, 140,141 and therefore reduce the domain errors significantly. This strongly improves the accuracy and robustness of the local methods.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of explicitly correlated approaches with local methods has been particularly successful . It has been found that the F12 terms not only reduce the basis set incompleteness errors, but also implicitly account for excitations to the orbitals outside the domains, , and therefore reduce the domain errors significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In the GEBF approach, the ground‐state energy of a target system can be obtained from the energies of a series of subsystems, each of which is embedded in the field of natural population analysis (NPA) point charges on the atoms outside of the subsystem to take the long‐range electrostatic interactions and polarization effects into account. Then, the total energy of the target system can be represented as, Etot=mMCmtrueE˜mtrue(mMCm1true)AB>AQAQB|boldqAboldqB| where M is the number of subsystems, Cm and trueE˜m are the coefficients and the energy (including self‐energy of point charges) of the mth embedded subsystems, respectively, and boldqA and QA are the coordinates of atom A and the point charge located on atom A, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the scalings of the conventional quantum chemistry methods, three categories of linear scaling algorithms have been implemented, including first‐principle linear scaling HF and DFT algorithms, local correlation post‐HF methods, and fragmentation‐based approaches . The first‐principle linear HF and DFT algorithms focus on the fast algorithms of integrals, Coulomb and exchange matrices, or the avoidance of the diagonalization of Fock matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation